PERCAKAPAN BAHASA INGGRIS ANTARA PENGEMUDI BECAK DAN PENJAGA TOKO DI KAMPUNG BATIK LAWEYAN-SURAKARTA - Sari Handayani; Veronika Unun Pratiwi (Widya Mandala Surabaya Catholic University, 2015)
The purpose of this research was peculiarly to provide pocket book as one media that can be used to improve English conversation and guiding skill for pedicab drivers and shopkeeper at batik tourism village of Laweyan Surakarta which include: 1) how to make a conversation, and 2) how to guide. Generally, it aimed to (1) develop the instruments of linguists’ test covering a) material design, b) linguist, c) tourism, and d) translation expert. (2) Carry out revision test, and (3) developing the final product of pocket book. This research was namely Research and Development (R & D). This research was done in developing product. Need analysis has become the basic instrument for the researcher in developing pocket book. Besides, theoretical and empirical study has helped the researcher to decide former pocket book design. The steps of the research covered 5 steps: 1) Former product analysis; 2) Developing former product; 3) expert validation and revision; 4) small-scale test and revision; 5) large-scale test and final froduct. Based on the research, it can be concluded that the using of pocket book was effective to improve the communication ability of the pedicab driver and shopkeeper at batik tourism village of Laweyan Surakarta The pocket book could help increasing the life-quality in case of finance, knowledge, and ethics for the pedicab driver snd shopkeeper in facing the foreign tourist. Key Words: pocket book, English conversation, guiding, pedicab driver, shopkeeper.